Cuestiones eticas problemáticas en la era de la informacion, internet y la world wide web - Luisa Montuschi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
– Advances in computer technology present many opportunities as well as dangers to individuals, organizations and the society as a whole. Many social values are challenged by the technology and its application to the work and private life of many individuals. New ethical issues have arisen that should be dealt with. The primary concerns are the problems of privacy, surveillance in the workplace, property, computer security, access and power. The increasing global character of Internet and the World Wide Web requires global moral norms and professional responsibility. The main challenge is to find a way in which social and ethical values could be incorporated in the new global society of digital technology.
Keywords: 330; Wissensgesellschaft; Internet; Ethik